2014
DOI: 10.1111/tmi.12264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Group A beta‐haemolytic Streptococcus isolated from children with acute pharyngotonsillitis in Aden, Yemen

Abstract: Abstractobjectives To estimate the prevalence of Group A beta-haemolytic streptococcus (GAS) and non-GAS infections among children with acute pharyngotonsillitis in Aden, Yemen, to evaluate the value of a rapid diagnostic test and the McIsaac score for patient management in this setting and to determine the occurrence of emm genotypes among a subset of GAS isolated from children with acute pharyngotonsillitis and a history of acute rheumatic fever (ARF) or rheumatic heart disease (RHD).methods Group A beta-hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(66 reference statements)
7
8
2
1
Order By: Relevance
“…Such indiscriminate use of antibiotics might contribute for the low carriage rate of GAS in the community. Similarly, 11.3% prevalence of GAS in our study was lower than the findings in Egypt, 22 Tunisia, 23 Yemen, 24 Brazil 25 and USA 26 where average prevalence of 17-58% was reported. Such variation may be due to differences in methodology, seasons of sample collection and geographical variation of study settings.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Such indiscriminate use of antibiotics might contribute for the low carriage rate of GAS in the community. Similarly, 11.3% prevalence of GAS in our study was lower than the findings in Egypt, 22 Tunisia, 23 Yemen, 24 Brazil 25 and USA 26 where average prevalence of 17-58% was reported. Such variation may be due to differences in methodology, seasons of sample collection and geographical variation of study settings.…”
Section: Discussioncontrasting
confidence: 85%
“…Similar findings were revealed in Canada, 30 USA 31-33 and Yemen. 24 However, it is important to know that the clinical variables that are predictor for GAS infection may vary with different GAS strains, geographic area and immunity profile of the study population. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Similar high rates (40% and 41.5%) of GAS pharyngitis have also been reported in other studies from Arab countries. 11 , 12 Previous studies on the prevalence of GAS in Egyptian children with sore throat reported that 24% 13 and 31.6% 14 had a positive throat culture. The high rate of GAS infection in our study may be due to the exclusion of children younger than 4 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Mısır'da 4-16 yaş arası hastaları kapsayan bir çalışmada ise GAS prevalansı %42.2 olarak bildirilmiştir (17) . Arap ülkelerinde de benzer yüksek prevalans oranlarının (%40-%41.5) bulunduğu çalışmalar yapılmıştır (18,19) . Ülkemizde, 0-18 yaş arası hastaları kapsayan bir çalışmada, GAS prevalansı %25 olarak belirlenmiş, bir başka çalışmada da prevalans benzer şekilde %24.6 bulunmuştur (6,20) .…”
Section: Discussionunclassified